Enhancement of phytolith-occluded carbon accumulation of Moso bamboo response to temperatures elevation and different fertilization - Liu, Lijun; Chang, Scott X.; Huang, Chengpeng; Zhi, Yuyou; Jie, Yang; Yu, Xiuling; Jiang, Peikun (Frontiers in Plant Science, 2023)
The accumulation of PhytOC in Moso bamboo could be a novel long-term carbon sequestration strategy. In this study, the effects of temperature change and different fertilization on PhytOC accumulation were investigated by a pot experiment. The pot experiment was established under different temperatures (with an average temperature of 16 and 20 ℃, respectively). The treatments of fertilization were control (CK), nitrogen fertilizers (N), silicon fertilizers (Si), and a combination of nitrogen and silicon (NSi). Despite the different fertilization, the PhytOC accumulation of the high- temperature group increases by 45.3 % on average compared with the low-temperature group, suggesting higher temperature is greatly beneficial to the PhytOC accumulation. Fertilization significantly increases the accumulation of PhytOC (increased by 80.7 % and 48.4 % on average for the low- and high-temperature group, respectively) compared with CK. However, the N treatment increased Moso bamboo biomass rather than PhytOC accumulation. The difference in the accumulation of PhytOC in Si and NSi was insignificant, indicating the combination of N and Si didn’t bring extra benefit to PhytOC accumulation. Our results further indicated the direct effects of fertilization on Moso bamboo, because different fertilization has very limited impact on the soil microbial community. Based on our study, we conclude that global warming poses a positive effect on promoting the long-term carbon sequestration of Moso bamboo. Finally, we proposed that the application of nitrogen fertilizer is a practical and effective method that is suitable for enhancing long-term carbon sequestration for Moso bamboo.